Rockport walking fitness test apps: application of cardiorespiration fitness test with rockport method android based - Muhammad Sigit Antoni; Guntur Guntur; Rifqi Festiawan; Arifin Ika Nugraha; Farid Imam Nurhadi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
This study aims to develop a feasible Android-based Rockport Walking Fitness Test application. This development research uses the ADDIE development model which consists of four stages of development: analysis, design, development and implementation, and evaluation. The Rockport Walking Fitness Test application contains the application menu, in the form of: (a) homepage, (b) Rockport Test, which contains a description page about the Rockport Walking Fitness Test, (c) guide, contains a guide page for application use and implementation of the Rockport Walking Fitness Test , (d) start the test, the data input page and timer that guides the implementation of the Rockport Walking Fitness Test, which continues to display the results of the Rockport Walking Fitness Test conducted, and (e) about, is a page that contains information about the Rockport Walking Fitness Test application and developer profile. Feasibility of the Rockport Walking Fitness Test application is assessed based on the assessment of material experts, obtained a score of 53.50 from a total score of 56.00 (very feasible category). Appraisal of feasibility by media experts obtained a score of 63.00 from a total score of 68.00 (very feasible category). The assessment of users in small group trials obtained a score of 42.17 from a total score of 52.00 (decent category). In the large group/field trial, the user assessment obtained a score of 49.77 from a total score of 52.00 (very feasible category). ROCKPORT WALKING FITNESS TEST APPS: APLIKASI TES KEBUGARAN KARDIORESPIRASI METODE ROCKPORT BERBASIS ANDROID AbstrakPenelitian ini bertujuan untuk mengembangkan aplikasi Rockport Walking Fitness Test berbasis Android yang layak. Penelitian pengembangan ini menggunakan model pengembangan ADDIE (Analysis, Design, Development and Implementation, Evaluation) yang terdiri dari empat tahap pengembangan yaitu analisis, perancangan, pengembangan dan implementasi, serta evaluasi. Gambaran umum aplikasi Rockport Walking Fitness Test memuat menu aplikasi, berupa: (a) beranda, (b) Rockport Test, yang berisi halaman deskripsi tentang Rockport Walking Fitness Test, (c) panduan, beirisi halaman panduan penggunaan aplikasi dan pelaksanaan Rockport Walking Fitness Test, (d) mulai tes, yaitu halaman input data dan penghitung waktu yang memandu pelaksanaan Rockport Walking Fitness Test, yang dilanjutkan menampilkan hasil Rockport Walking Fitness Test yang dilakukan, dan (e) tentang, merupakan halaman yang memuat informas mengenai aplikasi Rockport Walking Fitness Test serta profil pengembang. Kelayakan aplikasi Rockport Walking Fitness Test dinilai berdasarkan penilaian ahli materi, diperoleh skor sebesar 53,50 dari skor total sebesar 56,00 (sangat layak). Penilaian kelayakan oleh ahli media diperoleh skor sebesar 63,00 dari nilai skor total sebesar 68,00 (sangat layak). Penilaian para pengguna pada uji coba kelompok kecil diperoleh skor sebesar 42,17 dari nilai skor total 52,00 (layak). Pada uji coba kelompok besar/lapangan, penilaian pengguna diperoleh skor sebesar 49,77 dari nilai skor total 52,00 (sangat layak).